Analisis Daya Dukung Fondasi Foot Plate Menggunakan Metode Meyerhof dan Terzaghi Studi Kasus RSJ Mutiara Sukma - Sukma Dewi Rahmawati; Hariyadi Hariyadi; Hafiz Hamdani (Universitas Batanghari Jambi, 2026)
A foundation is a structural element that transfers building loads to the soil layer, thereby ensuring the stability of the construction. The foot plate foundation is a type of shallow foundation commonly used for low- to medium-rise buildings. This study aims to analyze the bearing capacity of foot plate foundations using the Terzaghi and Meyerhof methods and to compare the calculation results from both methods within the context of the construction of the Drug Rehabilitation Building at Mutiara Sukma Psychiatric Hospital, Mataram City. The study employs a quantitative method with a comparative analysis approach. The data utilized consists of secondary data from Cone Penetration Tests (CPT/sondir) and foundation design drawings. The Meyerhof and Terzaghi methods yielded different bearing capacity values at each testing point; these differences are attributable to the specific equations, soil parameters, and correction factors employed. This study could not determine the most representative method, as no validation was performed using load tests or actual settlement data. Regarding the allowable bearing capacity of the shallow foundations, the highest values were obtained using the Terzaghi method: 15,749.5 kN at point 1 (compared to 12,879.92 kN via Meyerhof). At point S2, the values were 3,180.57 kN (Terzaghi) and 2,202.51 kN (Meyerhof); at point S3, they were 6,580.49 kN (Terzaghi) and 5,582.46 kN (Meyerhof); and finally, at point S4, the values were 6,580.49 kN (Terzaghi) and 5,063.29 kN (Meyerhof).